A Shock Tube and Modeling Study about Anisole Pyrolysis Using Time‐Resolved CO Absorption Measurements. Issue 9 (30th June 2017) - Shu, Bo; Herzler, Jürgen; Peukert, Sebastian; Fikri, Mustapha; Schulz, Christof
ABSTRACT: The pyrolysis of anisole (C6 H5 OCH3 ) was studied behind reflected shock waves via highly sensitive absorption measurements of CO concentration using a rotational transition in the fundamental vibrational band near 4.7 µm. Time‐resolved CO mole fractions were monitored in shock‐heated C6 H5 OCH3 /Ar mixtures between 1000 and 1270 K at 1.3–1.6 bar. The decomposition of C6 H5 OCH3 proceeds exclusively via homolytic dissociation, with reaction rate k 1, forming methyl (CH3 ) and phenoxy (C6 H5 O) radicals. The subsequent decomposition of C6 H5 O by ring rearrangement and bond dissociation yields CO. To determine the rate constant k 2 of C6 H5 O decomposition avoiding secondary reactions, allyl phenyl ether (C6 H5 OC3 H5 ) was used as an alternative source for C6 H5 O. Its decomposition was studied between 970 and 1170 K at ∼1.4 bar. The potential‐energy surface of C6 H5 O dissociation has been reevaluated at the G4 level of theory. Rate constants determined from unimolecular rate theory are in good agreement with the present experiments. However, the obtained rates k 2 = 9.1 × 10 13 exp(−220.3 kJ mol −1 / RT )s −1 are significantly higher than those reported before (factor 6, 2, and 1.5 faster than those data reported by Lin and Lin, J. Phys. Chem . 1986, 90, 425–431; Frank et al., 1994; Carstensen and Dean, 2012, respectively). Good agreement was found between the measured CO concentration profiles and simulations based on the mechanism of Nowakowska et al. after substituting k 2 by the value obtained from experiments on C6 H5 OC3 H5 in this work. The bimolecular reaction of C6 H5 O and CH3 toward cresol was identified as the most important reaction influencing the CO concentration at longer reaction time.